Application of mnemonic technology in the educational process - Myrzabaev, A.B.; Sagadibek, A.S.; Shayakhmetova, M.N.; Tleuzhanova, K.T.; Mussina, V.T. (KU Publ., 2022)
Nowadays modern technologies allow people to be effective and perform several tasks simultaneously in a short time. However, the brain is a muscle and it also needs to be loaded and trained. Thus, if human beings rely only on technology and do not strain their brain at all, then this will lead to degradation. As a result, people can experience a deterioration in memory, the complexity of perception and assimilation of information. The article discusses ways to improve the memorization of human beings through different types of mnemonic technologies. The evidence that mnemonics has existed since ancient times and remains effective to this day has been proven. Also, mnemonic technology is classified into linguistic, visual, verbal and spatial methods and involved in education to make students more productive in their study. The authors provide examples for each method of mnemonics. Introduction ways of receptions to memorize in educational process of biology, chemistry and general training are treated.
Оқыту үрдісінде мнемоникалық техникаларды қолдану
Использование мнемотехники в процессе обучения
Keywords: mnemonics; new technique; memory; human development stages; digital amnesia; education; spatial mnemonics; visual mnemonics; verbal mnemonics